2005
DOI: 10.1021/ed082p1496
|View full text |Cite
|
Sign up to set email alerts
|

Napoleon's Buttons: Teaching the Role of Chemistry in History

Abstract: The nonscience majors course described here employs the book titled Napoleon's Buttons: How 17 Molecules Changed History as its key pedagogical tool. The book is an engaging account of 17 molecules or groups of molecules that have, like the tin buttons worn by Napoleon and his army, greatly influenced the course of history. Napoleon's Buttons frequently discusses how slight variations in the structure of a molecule can have a large impact on its properties. This theme provides the basis for both the classroom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…The use of popular books in college level chemistry courses has been previously described in this Journal. The book Napoleon's Buttons: 17 Molecules that Changed History has been incorporated into a nonmajors chemistry course 8 and an organic chemistry course. 9 The Poisoner's Handbook has been used in a first-semester general-organic-biochemistry course to encourage interest and provide context with each chapter providing a poisonous compound that was integrated into the regular course materials.…”
Section: ■ Background Popular Science Books In Chemistry Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of popular books in college level chemistry courses has been previously described in this Journal. The book Napoleon's Buttons: 17 Molecules that Changed History has been incorporated into a nonmajors chemistry course 8 and an organic chemistry course. 9 The Poisoner's Handbook has been used in a first-semester general-organic-biochemistry course to encourage interest and provide context with each chapter providing a poisonous compound that was integrated into the regular course materials.…”
Section: ■ Background Popular Science Books In Chemistry Coursesmentioning
confidence: 99%
“…The use of popular books in college level chemistry courses has been previously described in this Journal . The book Napoleon’s Buttons: 17 Molecules that Changed History has been incorporated into a nonmajors chemistry course and an organic chemistry course .…”
Section: Introductionmentioning
confidence: 99%
“…In several articles, authors describe aspects of popular culture (pop-culture) to teach chemistry using resources that are part of everyday life to engage students more effectively. Chemistry classes have been supplemented with material from arts such as music (including jazz and opera , ) and paintings (including fashion art), history, archeology, or literature. As examples, educators illustrated chemistry with a Shakespeare’s play while others found inspiration in detective cases where chemistry was used by the perpetrator of a crime or in their identification. , The chemical references from Ian Fleming’s James Bond series of novels were used to illustrate chemical reactions and substances (sedatives, rocket fuels, etc.). The Harry Potter novel series also offered an opportunity to reproduce wizardry experiments in a chemistry lab (e.g., with invisible and color-changing inks, colored flame in a jam-jar).…”
Section: Introductionmentioning
confidence: 99%
“…34 Research has shown that students often exhibit greater educational gains from student-generated instructional materials when compared to instructor-generated instructional materials. 34−37 Within the chemistry domain, instructors have incorporated a range of student-generated instructional materials including online homework questions, 38 e-books, 39,40 infographics, 41,42 3-D printed objects, 43 Wikipedia pages, 44−46 and videos. 47−53 The creation of studentgenerated videos, which has recently been reviewed by Gallardo-Williams et al, 53 has been shown to promote digital literacy, which is an important 21st century transferrable skill and to increase student engagement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Student-generated instructional materials refer to artifacts generated by students that are subsequently used in the learning process . Research has shown that students often exhibit greater educational gains from student-generated instructional materials when compared to instructor-generated instructional materials. Within the chemistry domain, instructors have incorporated a range of student-generated instructional materials including online homework questions, e-books, , infographics, , 3-D printed objects, Wikipedia pages, and videos. The creation of student-generated videos, which has recently been reviewed by Gallardo-Williams et al, has been shown to promote digital literacy, which is an important 21st century transferrable skill and to increase student engagement. In addition, this activity correlates with the science and engineering practice “Obtaining, Evaluating, and Communicating Information”, which is outlined in the Next Generation Science Standards …”
Section: Introductionmentioning
confidence: 99%